2021
DOI: 10.1111/ejn.15385
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of four different fluids on cerebral ischaemia/reperfusion injury in rats through stabilization of the blood–brain barrier

Abstract: Protecting the blood–brain barrier (BBB) is a potential strategy to treat cerebral ischaemic injury. We previously reported that hypertonic sodium chloride hydroxyethyl starch 40 (HSH) treatment alleviates brain injury induced by transient middle cerebral artery occlusion (tMCAO). However, other fluids, including 20% mannitol (MN), 3% hypertonic sodium chloride (HTS) and hydroxyethyl starch 130/0.4 solution (HES), have the same effect as HSH in cerebral ischaemia/reperfusion injury (CI/RI) remains unclear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The rat tMCAO model was constructed using the modified Zea Longa suture method as described previously (Li et al 2017 ; Liu et al 2017 , 2021 ; Shan et al 2021 ). Rats were anesthetized by administering an intraperitoneal injection of 1% pentobarbital sodium at a dose of 4.5 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…The rat tMCAO model was constructed using the modified Zea Longa suture method as described previously (Li et al 2017 ; Liu et al 2017 , 2021 ; Shan et al 2021 ). Rats were anesthetized by administering an intraperitoneal injection of 1% pentobarbital sodium at a dose of 4.5 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Microglia and astrocytes express a diverse set of TLRs [40]. NF-kB is a transcription factor linked to inflammation, oxidative damage, and apoptosis [40]. Our results showed that the brain tissues of the IR mice showed significantly higher mRNA expression of TLR2, TLR4, NF-kB, TNF-α, IL-6, and IL-1β.…”
Section: Discussionmentioning
confidence: 72%
“…TLR2 and TLR4 trigger the transcription factor NF-kB and increase the production of inflammatory cytokines [39]. Microglia and astrocytes express a diverse set of TLRs [40]. NF-kB is a transcription factor linked to inflammation, oxidative damage, and apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat tMCAO model was constructed by the modi ed Zea Longa suture method as described previously (Li et al, 2017;Liu et al, 2021;Shan et al, 2021). Rats were anesthetized by intraperitoneal injection of 1% pentobarbital sodium at a dose of 4.5 mL/kg.…”
Section: Transient Middle Cerebral Artery Occlusion (Tmcao) Modelmentioning
confidence: 99%